Efficacy of Topical Azithromycin 1% Ophthalmic Solution in the Treatment of Posterior Blepharitis - Sohail, Samreen; Yasin, Ubaidullah; Shabbir, Amina; Saleem, Iqra; Liaquat, Sheena; Zaman, Haziq (Indus Journal of Bioscience Research, 2025)
Objective: This study aims to address this gap by investigating the efficacy of topical azithromycin in infectious posterior blepharitis. Design of study: Descriptive study. Place and duration of study: AFIO, Rawalpindi between July, 2024 to January, 2025. Methodology: Individuals with posterior blepharitis who have been diagnosed, regardless of gender. Each participant was only allowed to participate in the study with one eye; if both eyes qualified, the left eye was chosen. Patients with a history of pregnancy, ocular infections, conjunctivitis, keratitis, or any ocular inflammations other than posterior blepharitis, as well as known allergies to azithromycin were excluded. Patients with a history of recent eye injuries or ocular surgery were also not included. For two days, 1% azithromycin eyedrops (Zithrosan) were given twice a day in the morning and evening. After that, they were given once a day in the evening for twelve days. Twice daily, each patient was told to apply a warm compress to the study eye. At baseline and following the two-week treatment period, all individuals had their ocular symptoms and MGD-related indicators assessed. Results: The prevalence of all four symptoms showed a significant reduction after treatment compared to before: sensitivity to light (p=0.0253), eyes grittiness (p<0.0001), burning sensation (p=0.0039) and blurred vision (p=0.0082). Significant improvements were observed in lid vascularity, lid plugging, and meibum grade on Day 14 (p=0.0001, 0.0001, and 0.0001, respectively). Conclusion: In summary, the current study shows that AZM treatment for blepharitis in MGD patients was effective when administered for 14 days.